Analisis Pengaruh Variasi Tekanan Pada Briket Cangkang Kemiri Terhadap Temperatur, Laju Pembakaran Dan Kadar Abu - Tonda, Naptalia; Jasron, Jahirwan Ut; Pell, Yeremias M.; Mangesa, Daud P. (Universitas Nusa Cendana, 2024)
In the process of making briquettes, there are still obstacles, namely, the printing process still uses traditional methods, and the existing briquette printing equipment is also not equipped with a hydraulic system and pressure gauge, so it requires more printing time. It cannot know how much pressure is applied during printing. A briquette printing machine equipped with a hydraulic system and pressure gauge is needed to simplify the briquette printing process and save energy. The aim of designing this briquette printing machine is to produce a press machine design with a hydraulic system equipped with a pressure gauge. The design method used in this research is the Shigley-Mitchell method. This briquette press has a length of 350 mm, a width of 450 mm, and a height of 840 mm. The mold cylinder has 16 mold cylinders. In one printing cylinder, it can produce briquettes weighing 52 grams with a height of 80 mm, so in one printing, this tool, with a printing time of 6.5 minutes, can produce 0.832 kg briquettes. The capacity of this briquette press per hour is 148 briquettes/hour.